Balancing and Alignment Analysis of Vertical Wind Turbine Helix Type and Savonius Type - Finali, Asmar; Wardhana, Prabuditya Bhisma Wisnu; Utomo, Rochmad Eko Prasetyaning; Yudha, I Gusti Ngurah Agung Satria Prasetya Dharma (TRANSMISI, 2023)
Electrical energy is one of the basic needs that is very important in life, in addition to the physiological development of living things, electricity is also an input for various efforts or activities in order to produce something for survival. Therefore, renewable energy that is more environmentally friendly and an inexhaustible source of energy is needed, namely wind energy. This power generator is called a wind turbine with a vertical shaft. This turbine converts wind energy into mechanical and electrical. In order to obtain a turbine design with high efficiency.  It is also necessary to balance and align each component frame attached to the turbine rotor to produce a perfect/ideal rotation, so as to minimize the occurrence of vibrations caused by the imbalance. the results of calculations with the analytical method on Darrius Helix type obtained value = 0.125 Newton, and = 0.175 Newton, and the value of the angle = 63.43490. Alignment testing is carried out to determine the value of the misalignment between one blade with another blade. The results of the balancing test with the blade ballast obtained additional value, the blade D was 70 grams and the results from the plate addition test were obtained according to the calculation of the analytical method but also less than the maximum requiring additional load on the blade body to get blade A = 12 grams, blade B = 0, blade C = 40 grams, and a spoon D = 90 grams. For the results and discussion of the balancing and alignment method on the savonius type using the static balancing and alignment method using a dial indicator, the values obtained are in the fields A and B, the addition of mass is 59,007 grams and 59.007 grams with angles A and B 11.88 ° , and the value The misalignment deviation in the A, B and center planes is A: 4mm, B: 0.04mm, middle: 0.52mm, while the shaft alignment value is 0 because the value of the alignment of the shafts is the same or parallel.